Facile one-pot synthesis of multi-yolk–shell Bi@C nanostructures by the nanoscale Kirkendall effect1. Issue 45 (7th June 2015) - Cui, C. M.; Guo, X. H.; Geng, Y. M.; Dang, T. T.; Xie, G.; Chen, S. P.; Zhao, F. Q.
<x xml:space="preserve">Abstract</x> Novel Bi@C multi-yolk–shell nanostructures with high catalytic activity were produced by the nanoscale Kirkendall effect.